Reconsidering Britain’s Civilizing Mission in India: Genuine Altruism or a Self-Serving Strategy? - Belkacem Belmekki (Atlantis)
Imperial apologists often ascribe Britain’s construction of its huge empire in the past to the noble urge to bring modernity and the benefits of Western civilization to less fortunate Africans and Asians, an enterprise historically named ‘civilizing mission’. These scholars tend to support their assertion by highlighting the achievements accomplished throughout the colonies, especially the spread of modern education among the natives as well as social reformism. Nonetheless, this position has been vehemently counter-argued by critics of empire, who cast doubt on the very genuineness of such a presumed altruistic drive. As such, within the framework of this controversial issue, this article attempts to reconsider the notion of benevolence as a central theme in the imperial discourse within the context of British India.